Synthesis, electrochemistry and In situ spectroelectrochemistry of novel tetra dimethyl 5-oxyisophthalate substituted Co(II), Mn(III), and mu-oxo-dimer Fe(III) phthalocyanines - ÖZKAYA, ALİ RIZA; ORMAN, EFE BATURHAN (ELSEVIER SCI LTD, 2015)
In this study, peripheral and non-peripheral tetra dimethyl 5-oxyisophthalate substituted cobalt(II), manganese(III) and mu-oxo-dimer Fe(III) phthalocyanines Were synthesized by the reaction of dimethyl 5-hydroxyisophthalate with 1,2-dicyano-4-nitrobenzene/1,2-dicyano-3-nitrobenzen in dry N,N-dimethylformamide in the presence of anhydrous potassium carbonate. All purified phthalocyanine compounds were characterized by using FT-IR, UV-visible, MALDI-TOF mass spectrometry and elemental analyses results. Electron transfer properties of all novel cobalt(II), manganese(III) and mu-oxo-dimer Fe(III)phthalocyanine complexes were investigated by voltammetric and in situ spectroelectrochemical measurements in nonaqueous solution medium. Complexes were observed to display both metal-based and phthalocyanine ring-based reduction and oxidation electron transfer processes. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Phthalocyanine; Manganese; Iron; Cobalt; Electrochemistry; Spectroelectrochemistry; HETERO-DINUCLEAR PHTHALOCYANINES; GAS-SENSING PROPERTIES; MANGANESE PHTHALOCYANINE; METAL-FREE; COBALT PHTHALOCYANINES; BEARING COUMARIN; OXYGEN; METALLOPHTHALOCYANINES; COMPLEXES; FILMS